KEABSAHAN HUKUM PENCANTUMAN SYARAT TAMBAHAN SEBELUM PENCAIRAN KREDIT - Sinaga, Roulinta Yesvery; Selfina Kuahaty, Sarah; Mumpuni Dyastuti, Risqi (LPPM, Universitas Muhammadiyah Riau, 2026)
Credit agreements are standard agreements, which have a tendency to have an imbalance in the bargaining position between creditors and debtors. The inclusion of additional terms in the credit agreement provides a dilemma for prospective debtors to accept or reject these terms. This position puts potential debtors at risk of being weak due to urgent financial conditions. This study aims to examine the legal validity of the inclusion of additional conditions before credit disbursement in bank credit agreements and analyze the position of the inclusion of additional conditions before credit disbursement as a form of application of the bank's prudential principle or the abuse of circumstances. The research was conducted using a normative juridical approach with literature studies and laws and regulations. The results of the study show that the inclusion of additional conditions before the credit agreement is valid and does not violate the provisions of Articles 1313 and 1320 of the Civil Code. Meanwhile, the inclusion of additional requirements if reviewed from Article 1338 paragraph 3 of the Civil Code, should be done in good faith, so that justice and balance are created and there is no indication of abuse of the situation.